2004
DOI: 10.1080/01926230490431475
|View full text |Cite
|
Sign up to set email alerts
|

The Candidate Neuroprotective Agent Artemin Induces Autonomic Neural Dysplasia without Preventing Peripheral Nerve Dysfunction

Abstract: Artemin (ART) signals through the GFRα-3/RET receptor complex to support sympathetic neuron development. Here we show that ART also influences autonomic elements in adrenal medulla and enteric and pelvic ganglia. Transgenic mice over-expressing Art throughout development exhibited systemic autonomic neural lesions including fusion of adrenal medullae with adjacent paraganglia, adrenal medullary dysplasia, and marked enlargement of sympathetic (superior cervical and sympathetic chain ganglia) and parasympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 90 publications
1
22
0
3
Order By: Relevance
“…Also, Gardell et al (2003) used artemin concentrations that were 300 times greater than that used in this study; this difference raises the possibility that high artemin concentrations have other effects that mask the hyperalgesic action reported here. However, in contrast to Gardell et al (2003), a similar study found that artemin injection [either intraperitoneally (5 m/kg) or intrathecally (10 g/d)] in rats did not block hyperalgesia produced by spinal nerve ligation (Bolon et al, 2004). This suggests that, even in the same species, the method of artemin application appears to dramatically alter efficacy.…”
Section: Discussionmentioning
confidence: 78%
“…Also, Gardell et al (2003) used artemin concentrations that were 300 times greater than that used in this study; this difference raises the possibility that high artemin concentrations have other effects that mask the hyperalgesic action reported here. However, in contrast to Gardell et al (2003), a similar study found that artemin injection [either intraperitoneally (5 m/kg) or intrathecally (10 g/d)] in rats did not block hyperalgesia produced by spinal nerve ligation (Bolon et al, 2004). This suggests that, even in the same species, the method of artemin application appears to dramatically alter efficacy.…”
Section: Discussionmentioning
confidence: 78%
“…To understand how this condition becomes intractable, interest has focused on the role of growth factors such as NGF and artemin in the development and maintenance of pain conditions. The effect of artemin on pain after nerve injury in the rat has been investigated using spinal nerve ligation (SNL) injury models (Gardell et al, 2003;Bolon et al, 2004). Gardell and colleagues (Malan et al, 2000;Gardell et al, 2003) reported that subcutaneous injection of artemin (1 mg/ kg) 3 d after nerve ligation significantly reduced tactile and thermal hypersensitivity within 24 h and normalized changes in spinal dynorphin levels, a pronociceptive agonist of the -opioid receptor that typically rises after SNL.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, dans un modèle murin de SLA, des souris transgéniques qui expriment des formes mutées de SOD1 (superoxyde dismutase-1) [8,9] (➜), quatre facteurs neurotrophiques se sont avérés être parmi les six traitements les plus efficaces testés (à l'exception, comme attendu, des modificateurs de SOD1) [10]. Nos données sur l'action préférentielle de l'HGF vis-à-vis des motoneurones LMC pourraient expliquer les puissants effets thérapeutiques de ce facteur contre la fonte de la masse musculaire et la parésie des membres, accord avec son expression restreinte dans les muscles des membres [7].…”
Section: Les Auteurs Déclarent N'avoir Aucun Lien D'intérêt Concernanunclassified
“…Enfin, l'ARTN apparaît comme un nouveau facteur de survie pour les motoneurones préganglionnaires du système parasympathique qui innervent les neurones postganglionnaires du côlon distal, de la vessie et des organes génitaux. Ceci est en concordance avec l'expression d'ARTN au niveau de ces organes [8], et également avec celle de son récepteur GFR3 dans les corps cellulaires et les axones des motoneurones préganglionnaires. Ces observations ont-elles des implications thérapeutiques ?…”
Section: Les Auteurs Déclarent N'avoir Aucun Lien D'intérêt Concernanunclassified
See 1 more Smart Citation